Mobile App Based Vehicle Services and Customer Satisfaction: A Case of Kathmandu Valley - Sharma, Pranawi (Nepalese Journal of Finance, 2024)
This study examines the Mobile app based vehicle services and customer satisfaction: A case of Kathmandu Valley. Customer satisfaction is the dependent variable. The selected independent variables are tangible, reliability, price, promotion and coupon redemption, and comfort. The primary source of data is used to assess the opinions of respondents regarding tangible, reliability, price, promotion and coupon redemption, and comfort. The study is based on primary data of 121 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of mobile app based vehicle services and customer satisfaction: A case of Kathmandu Valley.The study showed a positive impact of tangible on customer satisfaction. It indicates that higher the tangibility, higher would be the customer satisfaction. Similarly, the study showed a positive impact of reliability on customer satisfaction. It indicates that reliable information about the app based service leads to increase customer satisfaction. Likewise, the study revealed a positive impact of price on customer satisfaction. It indicates that affordable price leads to increase in customer satisfaction. Further, the study showed a positive impact of promotion and coupon redemption on customer satisfaction. It indicates that higher the numbers of promotion and coupon redemption, higher would be the customer satisfaction. In addition, the study showed a positive impact of comfort on customer satisfaction. It indicates that higher the comfort for travelling, higher would be the customer satisfaction.